Letters from Filadelfia : early Latino literature and the trans-American elite - Lazo, Rodrigo (Writing the early Americas., 2020)
"Letters from Filadelfia examines Spanish-language writing published in Philadelphia in the early nineteenth century by exiles, travelers, and immigrants who sought to influence sociopolitical conditions throughout the Americas. These political tracts, economic treatises, histories, novels, and books of poetry would have been considered seditious in the colonial territories administered by Spain, and they circulated throughout Central and South America and the Caribbean, helping to inspire independence all over the region. Lazo shows how this most American of cities opened conversations about political organization and economic conditions that crossed from the English language to Spanish and back"--